Faktor Penyebab Penyalahgunaan Narkoba Pada Remaja (Studi Pada 5 Remaja di Desa Hutagalung, Tarutung) - Syaharani; Bengkel (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This research is titled 'Factors Causing Drug Abuse Among Adolescents (A Case Study of 5 Drug Users in Hutagalung Siualuompu Village, Tarutung, North Tapanuli).' This study aims to identify the factors that contribute to social deviations among the adolescents in that village, particularly in the form of drug abuse. Hutagalung Siualuompu Village is known for its strong religious characteristics; however, the phenomenon of social deviation among its youth has become a concerning issue. The adolescents studied are those who are detained. The research method used is a qualitative approach with data collection techniques through interviews, observations, and document studies. The research findings indicate that social deviance among adolescents in this village is influenced by various factors, both internal such as personality, abilities, and individual psychological conditions, as well as external factors like family, peer relationships, education, mass media, and socioeconomic conditions. However, education and mass media do not significantly influence adolescents in social deviance related to drug abuse; rather, it is influenced by family factors, peer relationships, and socioeconomic conditions. In addition, the response of the community and local government to this issue is deemed insufficiently active, which exacerbates the situation. This research highlights the importance of the role of family and community in preventing and addressing deviant behavior among adolescents. Interventions that involve strengthening social values and increasing community awareness are expected to create an environment that supports positive development for adolescents.